The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1600-0668.2011.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation and the determinants of domestic endotoxin levels in mattress dust in Europe

Abstract: The incoherent observations of the health effects of endotoxin may be partly owing to the geographical heterogeneity of endotoxin exposure. Therefore, the observed variation should be considered in further studies. Measurements of indoor endotoxin are recommended as an indicator for the level of exposures of individual domestic environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 46 publications
(60 reference statements)
4
45
0
1
Order By: Relevance
“…These investigators cautioned that multiple shipping and long-term storage of the dust before endotoxin analysis may have diminished the integrity of the samples (14). In other studies performed in large U.S. inner cities (15,16) and in a European consortium study (2), investigators reported higher endotoxin levels in bedroom floor and/or bedding (Table 5).…”
Section: Discussionmentioning
confidence: 91%
“…These investigators cautioned that multiple shipping and long-term storage of the dust before endotoxin analysis may have diminished the integrity of the samples (14). In other studies performed in large U.S. inner cities (15,16) and in a European consortium study (2), investigators reported higher endotoxin levels in bedroom floor and/or bedding (Table 5).…”
Section: Discussionmentioning
confidence: 91%
“…too permissive). Epidemiologic studies relating endotoxin exposures to asthma outcomes 2, 14, 16, 17, 46, 47 have not adequately accounted for household endotoxin contained within bacterial OM.…”
Section: Discussionmentioning
confidence: 99%
“…24 In addition, most studies focused on investigating the health effects of endotoxin exposure, and detailed information about the measurement of endotoxins was often not available in the published paper.…”
Section: Concentration Of Endotoxins In Indoor Airmentioning
confidence: 99%